If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -19 = 7x + 17 Reorder the terms: -19 + 3x = 7x + 17 Reorder the terms: -19 + 3x = 17 + 7x Solving -19 + 3x = 17 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -19 + 3x + -7x = 17 + 7x + -7x Combine like terms: 3x + -7x = -4x -19 + -4x = 17 + 7x + -7x Combine like terms: 7x + -7x = 0 -19 + -4x = 17 + 0 -19 + -4x = 17 Add '19' to each side of the equation. -19 + 19 + -4x = 17 + 19 Combine like terms: -19 + 19 = 0 0 + -4x = 17 + 19 -4x = 17 + 19 Combine like terms: 17 + 19 = 36 -4x = 36 Divide each side by '-4'. x = -9 Simplifying x = -9
| 38+x+90=180 | | 2.3/18.4 | | 3(2+3K)+4(X-2)=5 | | 42=4y-14 | | 37+x+90=180 | | 30(10x-2)+x=56 | | -4z-2+8+5z= | | 86-x=266 | | 4(2x-3)+6=18 | | 38=2x-5y | | 5+3u=-1 | | 3(5x-9)=15x-27 | | 5x-7=7x-187 | | 2y+4=-2 | | 13=4m+7-m | | 7n-4+8n-3= | | 4.4q-3.7-5.5q=-0.1q-3.7 | | -19=5v+6 | | 0.08(y-8)+0.14y=0.18y-1 | | -14=-2+3v | | 6(6v+6)-5-6v=1 | | 5(x+6)=3(x+10)+2x | | (4x-4)+(3x+12)=0 | | 4x+x-6=5 | | 58=4x+10 | | -7(v+4)+4v+5=5v+11 | | 2(5r-9)= | | -3c-5-2c+6= | | 21x-11-12x=3(3x+5)+4 | | 1/9=5/3x | | (68-32)5/9 | | 8n-17n=18 |